Comparative Genomics Studies on the dmrt Gene Family in Fish - Dong, Junjian; Li, Jia; Hu, Jie; Sun, Chengfei; Tian, Yuanyuan; Li, Wuhui; Yan, Ningning; Sun, Chengxi; Sheng, Xihui; Yang, Song; Shi, Qiong; Ye, Xing (Frontiers in Genetics, 2020)
Doublesex and mab-3-related transcription factor (dmrt) genes are widely distributed across various biological groups and play critical roles in sex determination and neural development. Here, we applied bioinformatics methods to exam cross-species changes in the dmrt family members and evolutionary relationships of the dmrt genes based on genomes of 17 fish species. All the examined fish species have dmrt1–5 while only five species contained dmrt6. Most fish harbored two dmrt2 paralogs (dmrt2a and dmrt2b), with dmrt2b being unique to fish. In the phylogenetic tree, 147 DMRT are categorized into eight groups (DMRT1–DMRT8) and then clustered in three main groups. Selective evolutionary pressure analysis indicated purifying selections on dmrt1–3 genes and the dmrt1–3–2(2a) gene cluster. Similar genomic conservation patterns of the dmrt1–dmrt3–dmrt2(2a) gene cluster with 20-kb upstream/downstream regions in fish with various sex-determination systems were observed except for three regions with remarkable diversity. Synteny analysis revealed that dmrt1, dmrt2a, dmrt2b, and dmrt3–5 were relatively conserved in fish during the evolutionary process. While dmrt6 was lost in most species during evolution. The high conservation of the dmrt1–dmrt3–dmrt2(2a) gene cluster in various fish genomes suggests their crucial biological functions while various dmrt family members and sequences across fish species suggest different biological roles during evolution. This study provides a molecular basis for fish dmrt functional analysis and may serve as a reference for in-depth phylogenomics.